Minimally processed fruits with added probiotics: A review - Vanessa Caroline de Oliveira; Maria José do Amaral e Paiva; Daniele Juliana Rodrigues Gonçalves; Nataly de Almeida Costa; Érica Nascif Rufino Vieira; Bruno Ricardo de Castro Leite Júnior (The Journal of Engineering and Exact Sciences)
Probiotics can be like microorganisms that, when used for the health of living animals, confer health benefits. Probiotics are well known and well accepted by consumers, but they are mainly in dairy products, being a barrier to consumers who are lactose intolerant or allergic to milk proteins. In this sense, plant matrices are suitable to host probiotic microorganisms to increase the functional characteristics of minimally processed vegetables. In this way, this work reviews the main studies that show the potential of adding probiotics to minimally processed fruits. In addition, different ways of adding probiotics to plant matrices are discussed. In parallel, the review presents the viability of probiotics in minimally processed fruits, the challenges encountered and the best strategy for the incorporation of these microorganisms into plant matrices. Available research indicates that the intrinsic properties of vegetables contribute to an effective association of probiotics. Therefore, the possibility of using these matrices as carriers of probiotic strains is an opportunity to provide consumers with new probiotic foods that can be part of a varied diet, ensuring a regular intake of these microorganisms.